Subject Siam : family, law, and colonial modernity in Thailand - Loos, Tamara Lynn (Cornell University Press, 2006)
"Demonstrating the centrality of gender relations, law, and Siam's Malay Muslims to the history of modern Thailand, Subject Siam examines the structures and social history of jurisprudence to gain insight into Siam's unique position within Southeast Asian history. Tamara Loos elaborates on the processes of modernity through an in-depth study of hundreds of court cases involving polygyny, marriage, divorce, rape, and inheritance adjudicated between the 1850s and 1930s. Most important, this study of Siam offers a novel approach to the question of modernity precisely because Siam was not colonized yet was subject to transnational discourses and symbols of modernity."--Jacket